Analisis Penggunaan Bahan Ajar IPAS Berbasis STEAM Untuk Memfasilitasi Literasi Sains Pada Siswa Kelas V Sekolah Dasar - Trio Erawati Siregar; Anang Santoso; Radeni Sukma Indra Dewi (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This research aims to determine the presentation of STEAM and scientific literacy in students' books for science subjects. This research uses descriptive and qualitative research. This type of research is descriptive-qualitative research. This research uses the subjects of STEAM elements and scientific literacy, which are analyzed and appear in class V student books. The research instrument is an analysis sheet for STEAM elements and scientific literacy. We used a descriptive data analysis technique. The percentage category uses the percentage agreement value formula. This research shows that: (1) the STEAM elements that appear in student books, namely science elements, have a percentage of 47%, technology elements have a percentage of 73%, engineering elements have a percentage of 53%, art elements have a percentage of 37%, and mathematics elements have a percentage of 23%. (2) In the scientific literacy in class V students' books, the highest percentage of indicators that have appeared is attitude (83%), knowledge (36%), competence (33%), and context (23%). Therefore, students' books for science subjects include books that include elements of STEAM and scientific literacy.